A 20-year journey in transcatheter aortic valve implantation: Evolution to current eminence - Kalogeropoulos, Andreas S.; Redwood, Simon R.; Allen, Christopher J.; Hurrell, Harriet; Chehab, Omar; Rajani, Ronak; Prendergast, Bernard; Patterson, Tiffany (Frontiers in Cardiovascular Medicine, 2022)
Since the first groundbreaking procedure in 2002, transcatheter aortic valve implantation (TAVI) has revolutionized the management of aortic stenosis (AS). Through striking developments in pertinent equipment and techniques, TAVI has now become the leading therapeutic strategy for aortic valve replacement in patients with severe symptomatic AS. The procedure streamlining from routine use of conscious sedation to a single arterial access approach, the newly adapted implantation techniques, and the introduction of novel technologies such as intravascular lithotripsy and the refinement of valve-bioprosthesis devices along with the accumulating experience have resulted in a dramatic reduction of complications and have improved associated outcomes that are now considered comparable or even superior to surgical aortic valve replacement (SAVR). These advances have opened the road to the use of TAVI in younger and lower-risk patients and up-to-date data from landmark studies have now established the outstanding efficacy and safety of TAVI in patients with low-surgical risk impelling the most recent ESC guidelines to propose TAVI, as the main therapeutic strategy for patients with AS aged 75 years or older. In this article, we aim to summarize the most recent advances and the current clinical aspects involving the use of TAVI, and we also attempt to highlight impending concerns that need to be further addressed.